A educação especial na educação do campo: as configurações de uma escola da rede municipal de ensino - Kühn, Ernane Ribeiro (2017)
The present research is about special education in the context of field education in the Educational Network in the city of Santa Maria/RS, which is justified due to the fact that there are few studies involving the context of filed schools and students who are target of special education who study in these spaces. As general objective is to know the offer and organization of special education in a field school in the Educational Network in Santa Maria. As specific objectives: to analyze the enrollment flow of students who are target of special education in the period between 2010 to 2013; and also get to know the offer and organization of special education in the school and know how the process of identification and diagnosis of students who are target of special education takes place. The study used a qualitative investigative approach of a descriptive nature. In order to do that, a survey concerning the scientific production involving an interface between special education and field education was carried out, and also an analysis of the Microdata of the Basic Education School Census (BRAZIL) of the National Institute of Educational Studies and Research Anísio Teixeira (Inep). Using the statistical data, it was possible to have some primary knowledge of the field school in the Educational Network in Santa Maria/RS, as well as to identify the school which presents the highest incidence of students who are target of special education. Based on that, the interview was created and carried out with the teacher. The relations between special and the field education depicted the existence of public educational policies in both areas. It is possible to realize that they guarantee the access to the students who are target of special education and recognize the education in the field school, respecting their peculiarities. It was verified that the Intellectual Disability is the one with highest incidence in the investigated context. As to the offer and organization of the special educational service – it is carried out in a complementary way to the schooling, although recognizing the singularities of how a field school works. Producing the individualized support plan and the development of pedagogical actions in partnership with the other teachers who are involved in the school inclusion process of students point out the involvement of the teacher with the student’s process in order to recognize his educational evolutions. It was understood that the school fills in the School Census, having as basis the information concerning the clinical diagnosis and/or the pedagogical report of the special education teacher, reassuring the admission and the frequency of the student in the special educational service.